Implikasi Penambangan Emas Ilegal Pada Masyarakat Adat Yonamami Amazon Brasil - Diyani, Trini; Allagan, Tiurma Mangihut Pitta (UI Scholars Hub, 2022)
The study seeks to understand the implications of mining on the rights of the Yanomami Indigenous Peoples of theBrazilian Amazon. Brazil has great potential for mining activities in the future. However, in recent years there has been a large number of illegal gold mining activities contributing greatly to the environment both physically and socially. Illegal mining leads to clashes between miners and the Yanomami tribe as well as severe environmental degradation. These miners are estimated to account for about a third of Brazil's gold production. Illegal gold mining in the Amazon increases deforestation and water pollution resulting in deforestation of the Amazon jungle. The illegal gold mining that occurs in the Yanomami Indigenous Tribe has been contrary to the nawacita spirit of the International Labour Convention No. 169 of 1989. The Inter-American Commission on Human Rights (IACHR) recommends that the government take preventive and curative measures to protect the Yanomami indigenous area.